Community strategies for health promotion and prevention of chronic non-communicable diseases with a focus on physical activity and nutrition: the URO/FOCOS study protocol - Monsalves-Álvarez, Matías; Solis-Soto, María Teresa; Burrone, María Soledad; Candia, Alejandro A.; Jofré-Saldía, Emilio; Espinoza, Gabriela; Flores-Opazo, Marcelo; Puebla, Carlos; Valladares-Ide, Denisse; Jannas-Vela, Sebastián (Frontiers in Public Health, 2024)
Non-communicable diseases (NCDs) account for 71% of all annual deaths, totaling 41 million people worldwide. The development and progression of these diseases are highly related to the environment and lifestyle choices, among which physical inactivity and excess malnutrition stand out. Currently, in Chile, there is no evidence at the regional and local level on the impact of physical activity and healthy nutrition plans and interventions on health promotion, prevention, and timely treatment of NCDs. The following protocol delineates the URO/FOCOS (Universidad Regional de O'Higgins/FOrtaleciendo COmunidades Saludables- Regional University of O'Higgins/Strengthening Healthy Communities) study, which will assess pilot community intervention strategies using a participatory action research approach by identifying barriers and facilitators on the practice of physical activity and healthy eating habits. In this project, the community from the O'Higgins region will be involved throughout the entire research process to develop strategies that promote regular physical activity and healthy eating practices. We propose three interrelated strategies: 1) Participatory Action Research, 2) Community interventions for promoting physical activity and healthy nutrition practices, and 3) health education. The URO/FOCOS study offers a unique opportunity in the O'Higgins region to develop participatory strategies and interventions based on the community's needs and motivations with regard to physical activity and healthy eating habits. We believe these strategies will help to improve the community's overall health through effective changes in their decision and preferences toward a more active lifestyle and healthier nutrition practices.